Outlook and Challenges of Nano Devices, Sensors, and MEMS - Li, Ting.; Liu, Ziv.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides readers with an overview of the design, fabrication, simulation, and reliability of nanoscale semiconductor devices, MEMS, and sensors, as they serve for realizing the next-generation internet of things. The authors focus on how the nanoscale structures interact with the electrical and/or optical performance, how to find optimal solutions to achieve the best outcome, how these apparatus can be designed via models and simulations, how to improve reliability, and what are the possible challenges and roadblocks moving forward.
Introduction -- High-k dielectric for nanoscale MOS devices -- Performance, optimization, and reliability of FinFET devices -- Performance, optimization, and challenges of emerging nanowire field-effect transistors -- Graphene technology for future MEMS and sensor applications -- Nanoscale sensors for next-generation optical transceiver applications -- Nanoscale MEMS for future optical communication applications -- Nanoscale devices for biomedical applications -- Effect of nanoscale structure on reliability of nano devices and sensors -- Compact modeling of nano devices and sensors -- Three-dimensional TCAD simulation of nano semiconductor devices -- Fabrication of nano devices based on novel material -- Novel processing technology for fabricating nano devices and sensors -- Conclusions.
Keywords: Electronic circuits; Microtechnology; Microelectromechanical systems; Nanotechnology; Electronic Circuits and Systems; Microsystems and MEMS; Nanotechnology